Statistical prediction of environmental gamma radiation doses, in Perak, Malaysia - Zalina Rahmat; Ismail Bahari; Ismail Bahari; Redzuwan Yahaya; Amran Ab. Majid (Universiti Kebangsaan Malaysia, 2010)
The concentrations of Naturally Occurring Radioactive Material (NORM) and their corresponding terrestrial gamma radiation have been shown to be associated with certain lithology and soil types. A possible relationships among gamma radiation levels, and the lithology and soil types make it possible to predict ionizing radiation level of an area that cannot be directly measured. A study was carried out to statistically predict and validate environmental gamma radiation dose rates based on actual field measurements using a sodium iodide detector. Results obtained showed that the predicted dose rate (Dp) may be determined using a multiple correlation regression equation, Dp = 0.35DL + 0.82 Ds – 0.02, that integrates dose rates contributed by different lithological structures (DL) and soil types (Ds). Statistical analysis on 32 different lithology and soil type combinations showed that more than 50% of the predicted data were not significantly different from the data measured in the field. A predicted isodose map was subsequently plotted base on 4 dose rate classes ranging from 0.1 – 0.3 μSv h-1.